A Comparative Review of Pyroptosis in Mammals and Fish - Song Z; Zou J; Wang M; Chen Z; Wang Q (Dove Medical Press, 2022)
Zixi Song,* Jiahong Zou,* Mengya Wang, Zhenwei Chen, Qingchao Wang Engineering Research Center of Green Development for Conventional Aquatic Biological Industry in the Yangtze River Economic Belt, Ministry of Education, College of Fisheries, Huazhong Agricultural University, Wuhan, 430070, People's Republic of China*These authors contributed equally to this workCorrespondence: Qingchao Wang, Engineering Research Center of Green Development for Conventional Aquatic Biological Industry in the Yangtze River Economic Belt, Ministry of Education, College of Fisheries, Huazhong Agricultural University, Shizishan Street 1st, Hongshan District, Wuhan, Hubei, People's Republic of China, Tel +86-138 71499065, Fax +86-27 87282113, Email qcwang@mail.hzau.edu.cnAbstract: Pyroptosis is a form of programmed cell death, which is executed by gasdermin family proteins. Under the stimulation of pathogen- and/or damage-associated molecular patterns, pattern recognition receptors (PRRs) such as Nod like receptors could recruit apoptosis-associated speck-like protein containing a CARD (ASC) and pro-caspases to form inflammasomes and then activate caspases through various pathways. The activated caspases then cleave gasdermin family proteins, and N-terminal (NT) domains of gasdermins were released to form oligomeric pores, resulting in the increased membrane permeability, cell swelling, and final pyroptosis. During this process, caspases also promote the maturation and release of inflammatory cytokines such as IL-1β and IL-18, thus pyroptosis is also named inflammatory cell death. Unlike numerous gasdermin family proteins in mammals, only gasdermin E (GSDME) has been identified in fish. GSDME in fish can be cleaved by caspase-a/-b to release its NT domain and induce pyroptosis. Studies indicated that pyroptosis in fish mainly depends on NLR family pyrin domain-containing 3 (NLRP3) inflammasome. ASC and different caspase proteins also were identified in different fish species. The influences of pathogenic microorganism infection and environmental pollutants on fish pyroptosis were studied in recent years. Considering that fish living environment is affected by multiple factors such as water salinity, temperature, oxygen supply, and highly fluctuating food supply, the in-depth research about fish pyroptosis will contribute to revealing the mechanism of pyroptosis during evolution.Graphical Abstract: Keywords: pyroptosis, fish, gasdermin E, caspases